Safety and parasite clearance of artemisinin-resistant Plasmodium falciparum infection: A pilot and a randomised volunteer infection study in Australia - Watts, Rebecca E. (PLoS Med, 2020)
BACKGROUND: Artemisinin resistance is threatening malaria control. We aimed to develop and test a human model of artemisinin-resistant (ART-R) Plasmodium falciparum to evaluate the efficacy of drugs against ART-R malaria. METHODS AND FINDINGS: We conducted 2 sequential phase 1, single-centre, open-label clinical trials at Q-Pharm, Brisbane, Australia, using the induced blood-stage malaria (IBSM) model, whereby healthy participants are intravenously inoculated with blood-stage parasites. In a pilot study, participants were inoculated (Day 0) with approximately 2,800 viable P. falciparum ART-R parasites. In a comparative study, participants were randomised to receive approximately 2,800 viable P. falciparum ART-R (Day 0) or artemisinin-sensitive (ART-S) parasites (Day 1). In both studies, participants were administered a single approximately 2 mg/kg oral dose of artesunate (AS; Day 9). Primary outcomes were safety, ART-R parasite infectivity, and parasite clearance. In the pilot study, 2 participants were enrolled between April 27, 2017, and September 12, 2017, and included in final analyses (males n = 2 [100%], mean age = 26 years [range, 23–28 years]). In the comparative study, 25 participants were enrolled between October 26, 2017, and October 18, 2018, of whom 22 were inoculated and included in final analyses (ART-R infected participants: males n = 7 [53.8%], median age = 22 years [range, 18–40 years]; ART-S infected participants: males n = 5 [55.6%], median age = 28 years [range, 22–35 years]). In both studies, all participants inoculated with ART-R parasites became parasitaemic. A total of 36 adverse events were reported in the pilot study and 277 in the comparative study. Common adverse events in both studies included headache, pyrexia, myalgia, nausea, and chills; none were serious. Seven participants experienced transient severe falls in white cell counts and/or elevations in liver transaminase levels which were considered related to malaria. Additionally, 2 participants developed ventricular extrasystoles that were attributed to unmasking of a predisposition to benign fever-induced tachyarrhythmia. In the comparative study, parasite clearance half-life after AS was significantly longer for ART-R infected participants (n = 13, 6.5 hours; 95% confidence interval [CI] 6.3–6.7 hours) compared with ART-S infected participants (n = 9, 3.2 hours; 95% CI 3.0–3.3 hours; p < 0.001). The main limitation of this study was that the ART-R and ART-S parasite strains did not share the same genetic background. CONCLUSIONS: We developed the first (to our knowledge) human model of ART-R malaria. The delayed clearance profile of ART-R parasites after AS aligns with field study observations. Although based on a relatively small sample size, results indicate that this model can be safely used to assess new drugs against ART-R P. falciparum. TRIAL REGISTRATION: The studies were registered with the Australian New Zealand Clinical Trials Registry: ACTRN12617000244303 (https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=372357) and ACTRN12617001394336 (https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=373637).